The Role of Cardiopulmonary Exercise Test in IPF Prognosis - Triantafillidou, Christina; Manali, Effrosyni; Lyberopoulos, Panagiotis; Kolilekas, Likourgos; Kagouridis, Konstantinos; Gyftopoulos, Sotirios; Vougas, Konstantinos; Kotanidou, Anastasia; Alchanatis, Manos; Karakatsani, Anna; Papiris, Spyros A. (Pulmonary Medicine, 2013)
Background. In IPF, defects in lung mechanics and gas exchange manifest with exercise limitation due to dyspnea, the most prominent and disabling symptom. Aim. To evaluate the role of exercise testing through the 6MWT (6-minute walk test) and CPET (cardiopulmonary exercise testing) in the survival of patients with IPF. Methods. This is a prospective, observational study evaluating in 25 patients the relationship between exercise variables through both the 6MWT and CPET and survival. Results. By the end of the observational period 17 patients were alive (33% mortality). Observation ranged from 9 to 64 months. VE/VCO2 slope (slope of relation between minute ventilation and CO2 production), VO2 peak/kg (peak oxygen consumption/kg), VE/VCO2 ratio at anaerobic threshold, 6MWT distance, desaturation, and DLCO% were significant predictors of survival while VE/VCO2 slope and VO2 peak/kg had the strongest correlation with outcome. The optimal model for mortality risk estimation was VO2 peak/kg + DLCO% combined. Furthermore, VE/VCO2 slope and VO2 peak/kg were correlated with distance and desaturation during the 6MWT. Conclusion. The integration of oxygen consumption and diffusing capacity proved to be a reliable predictor of survival because both variables reflect major underlying physiologic determinants of exercise limitation.